PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT BATAM AUTO TEKNIKARYA - Michael; Evyanto, Winda (LPPM Universitas Putera Batam, 2022)
Batam City is experiencing an increase in the metal industry economy. The government paysattention to companies operating in the metal sector, because the metal industry can contribute tothe national economy. The metal industry is quite competitive, so there is a need for SNI standardsto ensure that the products produced are of good and reliable quality. In the city of Batam there is acompany called PT Batam Auto Teknikarya which is engaged in metal fabrication such as materialsderived from fabrication such as carbon plate, stainless, aluminum, pipe, and other types of metal.At PT Batam Auto Teknikarya, consumers in the company experienced a fairly large decline andoccurred every month since the beginning of 2021. This provides an overview and signs for thecompany where there are problems within the company so that consumers feel dissatisfied and donot make transactions return. Consumer satisfaction decreased due to various factors such asproduct quality that did not match expectations and service quality that was less communicative.Consumers do not make transactions again resulting in sales to the company also decreased. Thepopulation taken by the researcher is all consumers at PT Batam Auto Teknikarya totaling 137consumers and the sample technique of this research is the saturated sample. Based on the testresults, it is stated that simultaneously product quality and service quality have a positive andsignificant influence on consumer satisfaction